THE DIGITAL LEADERSHIP BEHAVIOURS OF X, Y, Z GENERATION NURSES IN THE DELIVERY OF HEALTH SERVICES - Sema Us̈tgor̈ul̈; Bulent Akkaya (Agora International Journal of Economical Sciences (AIJES), 2023)
Younger nurses are more active and agile in nursing leadership comparing to as senior nurses are about to retirement. Digital era and technology forces nurses to be more dynamic and adaptive. Thus, they try to behave as digital leaders. The aim of this study to link the relationship between young digital nurse leaders' organizational resilience and commitment in hospitals. To test this relationship, the data were collected from nurses in three groups: X, Y and Z generation. The data were collected by four scales and analysed by SPSS program. The results show that digital leadership has a positive effect on both organizational resilience and organizational commitment. Moreover, organizational resilience and organizational commitment is positively correlated. The young nurses have more digital leadership skills and behaviours comparing senior ones. But the perception of organizational resilience and commitment of the X generation nurses was higher than the Y and Z generations. The results of this study may guide to the managers of healthcare organization to pay attention young nurses in adapting technology and guide to senior nurses through applying digital leadership behaviours.
Keywords: 330